ChemInform Abstract: Liquid Phase Oxidation Chemistry in Continuous‐Flow Microreactors. Issue 6 (21st January 2016) - Gemoets, Hannes P. L.; Su, Yuanhai; Shang, Minjing; Hessel, Volker; Luque, Rafael; Noel, Timothy
Abstract: Review: 347 refs.